The Role of the Manager in the Middle East: An Empirical Study of Multinational Companies. Issue 4 (August 2019) - Mosbah, Aissa; Alharbi, Jaithen; Fetais, Abdulla; Alkandi, Ibrahim
Abstract: This article is an empirical investigation into the role of the CEO manager in the affiliates of multinational corporations operating in the Middle East. Grounded in a literature review of the reasons for employing either parent country nationals (PCNs) or host country nationals (HCNs) in top management position in foreign subsidiaries, a number of factors influencing the choice between these alternatives are identified. Using a data collected from 147 multinational companies (MNCs) operating in the Kingdom of Saudi Arabia (KSA), the influence of each of these factors on this selection is empirically tested with the help of primary data. The study proposed that the relationship between the home and host country managers could be linked to agency theory (with the 'classical' principal–agent relationship) and to resource dependency theory (implying relations between the branch and other partners based on interdependence). Our results show that the agency and resource dependency mechanisms are indeed used side by side and complementary to each other to exercise control. Home country managers can strategize to implement control by the informal and social means by positioning a sizeable number of managers from the home country within the subsidiary. Indeed, our results revealed this as true.